2019
DOI: 10.22226/2410-3535-2019-2-157-161
|View full text |Cite
|
Sign up to set email alerts
|

High strength and fatigue properties of Mg-Zn-Ca alloys after severe plastic deformation

Abstract: Magnesium alloys are the lightest metallic structural materials with an outstanding specific strength. This makes them appealing for a wide range of applications in "green" transportation where weight saving is of major concern. Another emerging application area for modern Mg-based alloys is in the biomedical domain where they are considered as bioabsorbable temporary implants, and where the worldwide market is expanding particularly rapidly in parallel with the surging research. Requirements for mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
0
5
0
1
Order By: Relevance
“…Эта проблема сейчас успешно решается за счет использования комплексной обработки, включающей такие передовые методы интенсивной пластической деформации, как изотермическая прокатка, ротационная ковка, всесторонняя изотермическая ковка, равноканальное угловое прессование и др. [5]. Однако вторая проблема, связанная с невысокими коррозионно-усталостными свойствами магниевых сплавов, до сих пор остается нерешенной.…”
Section: Introductionunclassified
“…Эта проблема сейчас успешно решается за счет использования комплексной обработки, включающей такие передовые методы интенсивной пластической деформации, как изотермическая прокатка, ротационная ковка, всесторонняя изотермическая ковка, равноканальное угловое прессование и др. [5]. Однако вторая проблема, связанная с невысокими коррозионно-усталостными свойствами магниевых сплавов, до сих пор остается нерешенной.…”
Section: Introductionunclassified
“…Additionally, excessive amounts of Mg2Ca reduces ductility and renders the alloy susceptible to localized degradation. Nevertheless, this phase reportedly does not form beyond a Zn/Ca atomic ratio of ~ 1.3 [16], [17], but was detected in an MZC alloy with 1.82 Zn/Ca ratio [10]. The nobler Ca2Mg6Zn3 phase on the other hand can act as a temporary barrier to localized corrosion [10].…”
Section: Properties Of Biodegradable Alloysmentioning
confidence: 97%
“…A ten-fold grain size reduction was achieved from 220m to ~ 20 -30 m. Post ECAP rotary swaging successfully increased the ultimate tensile strength of the alloy from 245 to 381 MPa, however this resulted in a reduction in ductility from about 28 -5 % elongation [16].…”
Section: Properties Of Biodegradable Alloysmentioning
confidence: 99%
“…Furthermore, study [36] showed that rolling followed by ECAP can increase the mechanical strength, ductility, and corrosion resistance of pure magnesium. In similar research [37], it has been demonstrated that a combination of ECAP and rotary forging in the magnesium alloy Mg-Zn-Ca (ZX40) led to significant grain refinement and accumulation of dislocations. This, in turn, resulted in increased tensile strength and fatigue limit values of 380 MPa and 115 MPa, respectively.…”
Section: Introductionmentioning
confidence: 96%